An Overview on Appraisal of Attitude in Narrative and Recount Text - Eka Surya Fitriani; Suriyadi; Rizky Vita Losi (ASIAN PUBLISHER, 2023)
This study provides a comprehensive overview of attitude appraisal within the context of narrative and recount texts. The study investigated to use attitude as components of evaluation through language usage in students' recount and narrative text. In this study, qualitative research techniques based on library research were applied. Data collection used documentation methods that were adapted from library sources. Data analysis employs content analysis approaches, where each source or piece of literature is modified and the context's applicability is assessed in light of literature from other books, journals, or studies. Ultimately, the findings emphasize the significance of attitude appraisal in narrative and recount texts, offering insights into the nuanced ways it shapes and enhances the reader's interpretative journey. Taken from four previous studies which had on Appraisal analysis, all data found the use of affect mostly in students’ writing in narrative and recount text. Reaching 50% among the other two types, judgment and appreciation, affect is one of the type of attitude in appraisal showing the way of writer in giving positive or negative feeling and emotion based on what they experienced.